Między katechizmem a biblioteką – w stronę inkluzyjnej pedagogiki religii - Humeniuk, Monika (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The task of religious education in its hermeneutic and critical approaches is to build discursive interpretations, and on their grounds - the communication communities inspired by the local traditions of reading the sacred books. Under this type of community, there would be social transformation for the empowerment and emancipation of every individual and social group. Hermeneutic and critical views of religious pedagogy are an invitation to construct open, dialogical and inclusive spaces of reflection on individual and social religiosity, orienting the processes of education to the self-understanding and criticality of their religious cognition. This kind of pedagogy of religion allows us to re-orient the theory and practice from the realm of dogma into the realm of ethics, appreciating the conscience and individual (self) responsibility of the subject of educational processes. The article attempts to theoretically describe such pedagogy, with its values, objectives and language.
Keywords: critical pedagogy of religion; emancipation; hermeneutic of religion; inclusion; radical hermeneutics; self-understanding; Gianni Vattimo; weak thought